Student Preception About Using E-Book and Printed Book of Modul Pembelajaran Bahasa Inggris Kelas Xi at SMA N. 3 Tondano - Possumah, Hideki Petrus Possumah; Oroh, Elisabeth Z.; Rorimpandey, Rinny S (Program Studi Pendidikan Bahasa Inggris, 2024)
Abstract : This research conducted a study on student perceptions of ebooks and printed books. The study involved 20 respondents and 20 questioners who answered statements about ebooks and printed books. The results showed that the majority of students agreed and strongly agreed with the statements about ebooks, with 15% of students feeling happy when reading using ebooks. However, the majority of students disagreed with the second indicator of printed books, with 50% disagreeing and 25% disagreeing. The majority of students also expressed negative opinions about printed books, with 71% and 29% responding negatively. The most positive response was in point 10, where 60% of students strongly agreed and 30% agreed that reading using an ebook was more efficient. This research found a significant comparison between students' perceptions of ebooks and printed books. In the first indicator, 80% of students responded positively to ebooks, while 29% responded positively to printed books. However, 20% of students responded negatively to ebooks and 71% to printed books. The majority of students preferred reading using ebooks in the first indicator, while 71% disliked printed books. The researcher concluded that of the 20 students, the majority prefered